Jasmine Toguchi, super sleuth - Florence, Debbi Michiko (Florence, Debbi Michiko. Jasmine Toguchi, 2017)
Jasmine has looked forward to spending Girls Day with her family and best friend, Linnie, but first her sister says she will not participate, and then Jasmine upsets Linnie. As her big weekend plans start to unravel, Jasmine must use her sleuthing skills to spot the clues around her-- and within herself. Then maybe, just maybe, she can put everything back in order before Girl's Day is over!